Remarkable Capacity for Anaerobic Oxidation of Methane at High Methane Concentration. Issue 21 (15th October 2019) - Bowles, M.W.; Samarkin, V.A.; Hunter, K.S.; Finke, N.; Teske, A.P.; Girguis, P.R.; Joye, S.B.
Abstract: Anaerobic oxidation of methane (AOM), a central process in the carbon cycle of anoxic environments, moderates the release of methane from soils and sediments to water bodies and, ultimately, the atmosphere. The regulation of AOM in the environment remains poorly constrained. Here we quantified AOM and sulfate reduction (SR) rates in diverse deep seafloor samples at in situ pressure and methane concentration and discovered that, in some cases, AOM exceeded SR rates by more than four times when methane concentrations were above 5 mM. Methane concentration also affected other carbon‐cycling processes (e.g., carbon assimilation) in addition to SR. These results illustrate that substantial amounts of methane may be oxidized independent of SR under in situ conditions, reshaping our view of the capacity and mechanism of AOM in methane‐rich environments, including the deep biosphere, where sulfate availability is considered to limit AOM. Plain Language Summary: At the high pressures that typify deep ocean sediment environments (approximately 10‐bar hydrostatic pressure for every 100 m in water depth), greater amounts of methane, and other gases, are dissolved in seawater and in sedimentary pore water compared to concentrations observed at sea level. Microbially mediated reactions that are influenced by methane concentration are thus quite sensitive to the methane concentration utilized in an experimental design. When deep sea sediments were subjected to more realistic methane concentration during high‐pressure incubations, rates of microbial processes that cycle carbon, particularly methane oxidation, increased. These patterns were not discovered previously because incubations at pressure were not performed routinely. The data reshape our understanding of methane dynamics in marine sediments. Key Points: Anaerobic methane oxidation exceeds sulfate reduction rates when microorganisms are subject to elevated methane concentrations Methane concentration changes have cascading effects on the microbially mediated cycling of carbon in sediments